2021
DOI: 10.1523/jneurosci.2551-20.2021
|View full text |Cite
|
Sign up to set email alerts
|

Evidence and Urgency Related EEG Signals during Dynamic Decision-Making in Humans

Abstract: A successful class of models link decision-making to brain signals by assuming that evidence accumulates to a decision threshold. These evidence accumulation models have identified neuronal activity that appears to reflect sensory evidence and decision variables that drive behavior. More recently, an additional evidence-independent and time-variant signal, called urgency, has been hypothesized to accelerate decisions in the face of insufficient evidence. However, most decision-making paradigms tested with fMRI… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 83 publications
1
15
0
Order By: Relevance
“…Using variants of AARM that instantiated different modes of simplicity bias, Galdo et al (2021) provided evidence that humans tend toward low-dimensional representations as they learn. One interpretation of these findings is that while humans strive to achieve high accuracy in a task setting, they concurrently seek to reduce time and resource expenditure on individual trials (Boureau et al, 2015; Cisek et al, 2009; Thura et al, 2012; Yau et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Using variants of AARM that instantiated different modes of simplicity bias, Galdo et al (2021) provided evidence that humans tend toward low-dimensional representations as they learn. One interpretation of these findings is that while humans strive to achieve high accuracy in a task setting, they concurrently seek to reduce time and resource expenditure on individual trials (Boureau et al, 2015; Cisek et al, 2009; Thura et al, 2012; Yau et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“… 16 , 17 Like the conceptual framework of SAT, temporal expectation has been implemented through an urgency signal which biases the decision variable toward earlier responses. 11 , 12 , 18 , 19 , 20 Intriguingly, recent experimental evidence interprets urgency as a multiplicative factor which amplifies sensory evidence, leading to faster decisions 21 , 22 as well as impacting evidence-independent motor preparation. 12 Overall, how experimental manipulations of subjects’ temporal expectation impact internal urgency is still a matter of debate.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a recent study that tested various parameters in a prior-cued perceptual discrimination task found strong support for an urgency signal across all tested combinations of task demands and evidence (Kelly et al, 2020). Other new work further corroborates the urgency gating model, showing that the buildup of evidence accumulation signals in parietal cortex correlates more strongly with the temporal profile of evidence accumulation predicted by the urgency gating model than by a constant evidence accumulation model (Yau et al, 2021). Thus, rather than decision makers simply adjusting the physiological value of the response-triggering threshold to allow for speeded responding, a number of other adjustments might occur.…”
Section: Neurophysiological Modifications To Model Specificationsmentioning
confidence: 59%